Winter ecology of the Porcupine caribou herd, Yukon: Part III, Role of day length in determining activity pattern and estimating percent lying - Russell, D. E.; Martell, A. M. (Rangifer, 1986)
Data on the activity pattern, proportion of time spent lying and the length of active and lying periods in winter are presented from a 3 year study on the Porcupine caribou herd. Animals were most active at sunrise and sunset resulting in from one (late fall, early and mid winter) to two (early fall and late winter) to three (spring) intervening lying periods. Mean active/lying cycle length decreased from late fall (298 mm) to early winter (238 min), increased to a peak in mid winter (340 min) then declined in late winter (305 min) and again in spring (240 min). Mean length of the lying period increased throughout the 3 winter months from 56 min m early winter to 114 min in mid winter and 153 min in late winter. The percent of the day animals spent lying decreased from fall to early winter, increased throughout the winter and declined in spring. This pattern was related, in part, to day length and was used to compare percent lying among herds. The relationship is suggested to be a means of comparing quality of winter ranges.